From the soil to the table - Yusop, Mohd Khanif (2005)
Soil is the most important resource for food production. The increase in the world population puts pressure on the soil resource to continuously provide food security for the population. The per capita arable land is 0.29 ha per capita and it is expected to reduce due to population increase, land degradation processes and competition for non-agriculture land use. The agricultural sector has been successful to continuously supply food for the growing population. This is brought about by the green revolution resulting from technological improvement through advancement in scientific knowledge. With more constraints and greater challenges the agriculture sector requires more efficient and productive technology. Since horizontal increase through expansion of arable land is restricted the increase in food production has to be achieved vertically by increasing soil productivity. The use of fertilizer for improvement of soil productivity is widely practiced and N fertilizer is the most important fertilizer use world wide. The use of N fertilizer has no doubt increase the soil productivity; however it has also created serious environmental problems. The efficiency of N fertilizer is often low due to losses through denitrification, volatilization, and leaching and clay fixation. The N that leaks to the environment causes serious environmental problems such as ground water pollution, emission of greenhouse gases, eutrophication and nitrate pollution. For sustainable N management, the N loss has to be minimized to subsequently increase N fertilizer efficiency. Co-applying urea with selected cations, micronutrients and urease inhibitors can effectively improve urea efficiency. It was also shown that rice yield was not affected when irrigation was applied only at soil saturation level instead of continuous flooding at 5-10cm as currently practiced. Thus, potentially, tremendous amount of irrigation water can be saved and more area of land can be used for rice production .The public awareness on the importance of soil resource for food production and human survival should be provided through the education system. Research for public good on sustainable soil management must be given top priority alongside the market driven research, to ensure the agriculture sector continue to supply us with food from the soil to the table.